A study of the radio frequency spectrum emitted by high-energy air showers with LOFAR - Rossetto, L.; Buitink, S.; Corstanje, A.; Enriquez, J. E.; Falcke, H.; Hörandel, Jörg R.; Nelles, Anna; Rachen, J. P.; Schellart, P.; Scholten, O.; Ter Veen, S.; Thoudam, S.; et al. (Proceedings of Science, 2015)
The LOw Frequency ARray (LOFAR) is a multipurpose radio antenna array aimed to detect radio signals in the frequency range 10 - 240 MHz, covering a large surface in Northern Europe with a higher density in the Northern Netherlands. The detection of the radio signal emitted by extensive air showers allows to reconstruct the geometry of the observed cascade. Thus, several properties of primary particles (e.g. arrival direction, mass composition) can be inferred. We describe a study of several geometrical parameters of the radio signal emitted by extensive air showers propagating in the atmosphere, and their correlation with the observed radio frequency spectrum. In order to find the best parameters that describe the correlation between primary cosmic ray information and the emitted radio signal, a preliminary study on simulated events has been done. Monte Carlo simulations of radio signals have been produced by using the CoREAS code, a plug-in of the CORSIKA particle simulation code. The final aim of this study is to find a method to infer information of primary cosmic rays in an independent way from the well-established fluorescence and surface detector techniques, in view of affirming the radio detection technique as reliable method for the study of high energy cosmic rays.
CRIS-Team Scopus Importer:2023-08-15